TMEM100 Regulates Neuropathic Pain by Reducing the Expression of Inflammatory Factors - Huifei Cui; Zhaoyang Guo; Zhu Guo; Zuoran Fan; Nana Shen; Xiaoying Qi; Yuanye Ma; Youfu Zhu; Xiaolin Wu; Bohua Chen; Hongfei Xiang (Hindawi Limited, 2023)
There is no effective treatment for peripheral nerve injury-induced chronic neuropathic pain (NP), which profoundly impacts the quality of life of those affected. Transmembraneprotein100 (TMEM100) is considered to be a pain regulatory protein and is expressed in the dorsal root ganglion (DRG) of rats. However, the mechanism of pain regulation and the expression of TMEM100 following various peripheral nerve injuries are unclear. In this study, we constructed two pain models of peripheral nerve injury: tibial nerve injury (TNI) and chronic constriction injury (CCI). This study found that the Paw Withdrawal Mechanical Threshold (PWMT) and Paw Withdraw Thermal Latency (PWTL) of the rats in the two pain models decreased significantly, and the expression of TMEM100 in the DRG of two groups also decreased significantly. Furthermore, the decrease in the CCI group was more obvious than in the TNI group. There was no significant statistical significance (P>0.05). We constructed an adeno-associated virus 6 (AAV6) vector expressing recombinant fluorescent TMEM100 protein and injected it into the sciatic nerve (SN) of two pain models: CCI and TNI. PWMT and PWTL were significantly increased in the two groups, along with the expression of TMEM100 in the spinal cord and DRG. It also significantly inhibited the activation of microglia, astrocytes, and several inflammatory mediators (TNF- α, IL-1 β, and IL-6). In summary, the results of this study suggested that TMEM100 might be a promising molecular strategy for the treatment of NP, and its anti-inflammatory effects might play an important role in pain relief.